Фрагментація міжнародного права: методологічний аспект - Плотніков, Олексій Вікторович; Плотников, Алексей Викторович; Plotnikov, Aleksej (Одеса : Юрид. л-ра, 2012)
The article considers the mechanism of fragmentation of international law under the conditions of globalization of the world system. The article demonstrates the role and primary strategies of the subjects of international law within the framework of its fragmentation, defines and explains the notion of factors of fragmentation.
Плотніков О. В. Фрагментація міжнародного права: методологічний аспект / О. В. Плотніков // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 200-208.
Keywords: фрагментація міжнародного права; глобалізація; міжнародно-правова система; фактор фрагментації; механізм фрагментації міжнародного права; фрагментация международного права; глобализация; международно-правовая система; фактор фрагментации; механизм фрагментации международного права; Fragmentation of international law; globalization; international legal system; factors of fragmentation.; mechanism of fragmentation of international law